Shear wavelength estimation based on inverse filtering and multiple-point shear wave generation - Kitazaki, Tomoaki; Kondo, Kengo; Yamakawa, Makoto; Shiina, Tsuyoshi (Japanese Journal of Applied Physics, 2016)
Elastography provides important diagnostic information because tissue elasticity is related to pathological conditions. For example, in a mammary gland, higher grade malignancies yield harder tumors. Estimating shear wave speed enables the quantification of tissue elasticity imaging using time-of-flight. However, time-of-flight measurement is based on an assumption about the propagation direction of a shear wave which is highly affected by reflection and refraction, and thus might cause an artifact. An alternative elasticity estimation approach based on shear wavelength was proposed and applied to passive configurations. To determine the elasticity of tissue more quickly and more accurately, we proposed a new method for shear wave elasticity imaging that combines the shear wavelength approach and inverse filtering with multiple shear wave sources induced by acoustic radiation force (ARF). The feasibility of the proposed method was verified using an elasticity phantom with a hard inclusion.